Economics of Biodiesel Production in the Context of Fulfilling 20% Blending with Petro-Diesel in Nepal - Parajuli, Ranjan (Journal of the Institute of Engineering, 2014)
The article has attempted to introduce Jatropha curcas as one of the energy resource for partially substituting Petro-diesel in Nepal and is prepared to provide preliminary insight on the economics of biodiesel production in the country. There have been increasing trend of automobiles in the last two decades, which has also increased the total import volume of Petro-diesel in Nepal. The dependency on imported Petro-diesel and its escalating price is adversely affecting the national economy. To fulfill the 20% blending requirement of the Petro-diesel consumed in 2011 in the country, 4% of the uncultivated land of the country (representing terrain and hills only) are sufficient. With this realization, this article is prepared by the development of different scenarios in regard to substitution of 20% Petro-diesel in the country. The Scenarios basically comprise of price of seedlings required for cultivation, different yield of Jatropha plant, and the price of raw oil seeds required for processing. Prognosis of Petro-diesel consumption in the next 20 years is carried out considering the average growth rate of its sales in the last decade in the country, and further required volume of biodiesel required for blending is estimated. Techno-economic analysis carried out in this article has revealed that biodiesel can be economically produced with input parameters (plant yield greater than 2 kg/plant and with the price of oil seeds lower than 0.22 USD/kg). The return on the investment in the bio diesel production and its utilization is also positive with these input parameters. The study estimated that production of biodiesel in the present context of increasing fuel prices and depleting resources, is an economically viable option, however, there is need of strong policy to entertain potential entrepreneurs and farmers for generating resource required for the partial substitution and also to look after the issues of food insecurity during the process of generating this resource. DOI: http://dx.doi.org/10.3126/jie.v10i1.10881 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 80–93